PENGARUH LABA BERSIH DAN ARUS KAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rina Nur Aisyah; Reina Damayanti; Emma Lilianti (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This study aims to determine the effect of Net Profit, Operating Cash Flow (AKO), Investing Cash Flow (AKI), and Financing Cash Flow (AKP) on Stock Prices of the chemical sector listed on the BEI for the 2016-2020 period with a population of 12 companies and 45 samples for 5 years. The data analysis in this study is a statistical analysis by collecting data through the data testing stage, namely: Normality Test, Multicollinearity Test, Heteroscedasticity, Auto-correlation Test, Regression Analysis Method, and Hypothesis Testing Test (partial and simultaneous) using the SPSS 25 software. The results of this study show that Net Income and Investing Cash Flow (AKI) have a significant effect on Stock Prices, meanwhile, Operating Cash Flow (AKO), and Financing Cash Flow (AKP) have no significant effect on Stock Prices. Net Profit, Operating Cash Flow (AKO), Investing Cash Flow (AKI) and Financing Cash Flow (AKP) simultaneously have significant effects on Stock Prices. Investing Cash Flow (AKI) is the dominant factor influencing Stock Price. Keywords: Net Profit; Operating Cash Flow; Investing Cash Flow; Financing Cash Flow, Stock Prices